Energy Management Strategy for Electric-Driven Lifting Systems in Heavy Agricultural Machinery - Zhao, Zhiheng; Ye, Guiyou; Li, Gaowei; Gao, Gongru; Fang , Xingyu; Li, Baogang (International Journal of Mechanical and Electrical Engineering, 2024)
In this paper, an innovative method for energy recovery and management of the electronically controlled suspension system is proposed and simulated using MATLAB/Simulink, with the aim of enhancing energy efficiency and environmental sustainability. This method employs an integrated control approach based on force-position for tillage depth control. When the tractor suspension is positioned above the soil surface and descending, the PMSM switches to generator mode and uses the PMSM for energy recovery. The simulation results demonstrate the viability of energy recovery in heavy agricultural machinery, offering novel ideas and techniques for effective energy management in such equipment.